Relationships between climate and double rings in Quercus ilex from northeast Spain - Campelo, F.; GUTIÉRREZ, E.; Ribas, M.; Nabais, C.; Freitas, H. (Canadian Journal of Forest Research, 2007)
The influence of climatic factors on tree-ring width and the formation of double rings was studied in Quercus ilex L. growing in a coppice stand left unmanaged for 22 years. Ten trees were felled and discs were taken every 30 cm from bole and dominant branches. Dendrometer bands were installed on 10 nearby trees and the data recorded were used to confirm the accuracy of our tree-ring identification. They were also used to relate the seasonal radial growth pattern to double-ring formation. Double rings were frequent and occurred consistently along the stem. Two types of double rings could be recognized according to their width: type I, with the extra growth band accounting for approximately 50% of the tree ring; and type II, with a narrow extra growth band. Type I double rings were formed when approximately 1/2 of the growing-season precipitation occurred during the second growth period of the season and after the summer drought. Type II double rings occurred when approximately 1/3 of the precipitation in the growing season occurred after the summer drought. The formation of double rings was triggered by rainfall in summer and the extra growth-band width was related to summer and autumn environmental conditions. Double rings in Q. ilex can potentially be used in dendroclimatological studies, as they are formed in response to climatic conditions within the growing season.
doi: 10.1139/X07-050doi: 10.1139/X07-050The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: chronology (voyant); double rings; Drought; growth pattern; growth rings; Precipitation; Quercus ilex